Association Between Non-Recovered Contrast-Associated Acute Kidney Injury and Poor Prognosis in Patients Undergoing Coronary Angiography - Zhou, Dianhua; Lun, Zhubin; Wang, Bo; Liu, Jin; Liu, Liwei; Chen, Guanzhong; Ying, Ming; Li, Huanqiang; Chen, Shiqun; Tan, Ning; Chen, Jiyan; Liu, Yong; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Previous studies have shown that renal function recovery after acute kidney injury was associated with decreased risk of all-cause mortality. However, little is known about the correlation between renal function recovery and long-term prognosis in patients with contrast-associated acute kidney injury (CA-AKI) undergoing coronary angiography (CAG). Methods We retrospectively enrolled 5,865 patients who underwent CAG. CA-AKI was defined as an increase ≥ 50% or ≥ 0.3 mg/dL from baseline in the 72 hours post procedure. Recovered CA-AKI was defined as serum creatinine drops to baseline or no CA-AKI level. The first endpoint was long-term all-cause mortality. Kaplan-Meier analysis and Cox regression analysis were used to investigate the association between kidney function recovery and long-term mortality. Results During the median follow-up period of 5.25 years, the overall long-term mortality was 20.07%, and the long-term mortality in patients with recovered CA-AKI and non-recovered CA-AKI were 17.46% and 27.44%, respectively. After multivariate Cox hazard regression, non-recovered CA-AKI was significantly associated with long-term mortality, while the recovered CA-AKI was not (recovered CA-AKI vs. no CA-AKI, hazard ratio [HR]= 1.06, 95%CI: 0.81-1.39, P=0.661; non-recovered CA-AKI vs. no CA-AKI, HR= 1.39, 95%CI: 1.21-1.60, P<0.001, respectively). In the subgroup of CAD, recovered CA-AKI and non-recovered CA-AKI were both associated increased risk of long-term all-cause mortality. However, in other subgroup analyses, just non-recovered CA-AKI was associated with increased risk of long-term all-cause mortality Conclusions Our results found that non-recovered CA-AKI is significantly associated with long-term mortality. In patients with CAD, recovered CA-AKI can still increase the risk of all-cause mortality. Clinicians need to pay more attention to patients suffered from CA-AKI whose kidney function has not recovered. In addition, active prevention treatments should be takes in patients with CAD.